Novel mutations in ATP7B in Chinese patients with Wilson's disease and identification of kidney disorder of thinning of the glomerular basement membrane - Xu, Hongliang; Lv, Hanyu; Chen, Xin; Lian, Yajun; Xing, Guolan; Wang, Yingzi; Hu, Ruimin (Frontiers in Neurology, 2023)
Introduction Wilson's disease is an autosomal recessive disorder caused by ATP7B pathogenic mutations. The hallmark of this disorder mainly consists of liver involvement, neurologic dysfunction and psychiatric features. In addition, the kidneys can also be affected by excessive copper deposition. Methods A total of 34 patients clinically diagnosed with WD were recruited. They underwent ATP7B gene sequencing and clinical data of symptoms, examination, and treatment were collected. Moreover, renal pathology information was also investigated. Results We identified 25 potentially pathogenic ATP7B variants (16 missense, 5 frameshift, 3 splicing variants and 1 large deletion mutation) in these 34 WD patients, 5 of which were novel. In our cases, the most frequent variant was c.2333G>T (R778L, 39.06%, exon 8), followed by c.2621C>T (A874V, 10.94%, exon 11) and c.3316G>A (V1106I, 7.81%, exon 11). Furthermore, we described the thinning of the glomerular basement membrane as a rare pathologically damaging feature of Wilson's disease for the first time. Additionally, two patients who received liver transplant were observed with good prognosis in present study. Discussion Our work expanded the spectrum of ATP7B variants and presented rare renal pathological feature in WD patients, which may facilitate the development of early diagnosis, counseling, treatment regimens of WD.